The Role of Planned Behavior in Predicting Customer Orientation - Hasanbarog, Zhila Mahrooz; Rasouli, Eshagh; Ardabili, Farzad Sattari; Azadi, Benham (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this qualitative research was to investigate the role of planned behavior in predicting customer orientation in the Iranian gas industry. The participants were 17 experts from the National Iranian Gas Company who were selected using purposive sampling and based on theoretical saturation. Data were collected using in-depth semi-structured interviews and were analyzed using thematic analysis and MAXQDA software.
Keywords: behavior prediction; planned behavior; customer orientation; gas industry